MR enterography versus capsule endoscopy in paediatric patients with suspected Crohn's disease. - Casciani E; Masselli G; Di Nardo G; Polettini E; Bertini L; Oliva S; Floriani I; Cucchiara S; Gualdi G; Casciani, Emanuele; Masselli, Gabriele; Di Nardo, Giovanni; et al. (European Radiology, 2011)
Objective: The aim of this prospective study was to compare the diagnostic yield of MR enterography (MRE) with small-bowel capsule endoscopy (SBCE) in paediatric patients with suspected Crohn's disease (CD).Methods: Paediatric patients with suspected CD were considered eligible to be enrolled in the study. All patients underwent diagnostic work-up including 1.5-T MRE, ileo-colonoscopy and oesophagogastroduodenoscopy. SBCE was not performed if MRE showed SB stricture or extra-intestinal findings consistent with symptoms.Results: Sixty consecutive paediatric patients (36 male; average age 14) were enrolled into the study. A positive diagnosis for CD was made in 19 patients, 29 had a negative result and 12 were affected by other gastro-intestinal conditions. SBCE was performed in 37 patients (61.7%); 23 patients were excluded (strictures in five, extra-intestinal findings in 11 and parents' refusal in seven cases). The accuracy, sensitivity, and specificity of MRE and SBCE were 98.3%, 100%, 97.6%, and 91.9%, 90.9%, 92.3%, respectively.Conclusion: Both MRE and SBCE are accurate methods for patients with suspected CD. MRE can be used as a primary imaging technique in suspected CD, in that it allows access to the ileal stricture, which forms a contra-indication for SBCE and provides extra-intestinal information.